Wide-angle resonance of a photonic crystal surface mode under a surface termination and its influence on imaging. (6th December 2016) - Hu, Hengrun; Liu, Hongmei; Qing, Yun; Cheng, Lu-Teng; Song, Weiwei; Yang, Xu; Jiang, Wei; Rao, Wei-Feng
Abstract: We have developed a semi-analytical approach to the modulation transfer function (MTF) for negative-index flat lenses based on photonic crystals (PhCs). Contributions of various PhC modes to the MTF have been identified and analyzed. With a certain surface termination, a high-order PhC surface mode can be tamed to produce a broad angular resonance. As such, the isotropy of the image field can be significantly enhanced, resulting in an ideal image formation with nearly perfect outgoing circular wavefronts. Ray-optics analysis has also been utilized to assist the design of a negative-index flat lens. Finite-difference time domain simulations confirm the effectiveness of PhC lens designed by this semi-analytic approach to the MTF.